(untitled) (Research, Society and Development, 2022)
A common problem in many Brazilian municipalities is the presence of soil erosion, which can lead to material losses and even loss of life. The main intervening factor in this phenomenon is the greater or lesser resistance of the soil to the action of water, which results in erodibility, defined as a soil attribute that represents its vulnerability to the removal of particles. Several mathematical models have been elaborated and developed to estimate the potential of soil erosion in different spatial and temporal scales. The objective of the present study was to present an evaluation of soil erodibility in the Urban Watershed of the Carneirinhos Stream, in the city of João Monlevade, state of Minas Gerais, through the characterization and analysis of erosion indicators in the watershed, using geotechnologies . The study showed that these tools were efficient in the interpolation of different thematic data and in the generation of new cartographic products allied to the Universal Soil Loss Equation (USLE), developed in the US Department of Agriculture, from which the factors R, K, LS and CP applied in the USLE were determined. The final result showed that the erosion rate ranged from values close to zero to 23,154 ton/ ha-1/year-1, and the areas classified as moderate to high are the same as those with high slope. The results showed that the areas identified as having greater erosive susceptibility also present other factors that contribute to this process, such as the type of soil, erosivity, steep slopes and little vegetation cover.